IMPLEMENTASI TEKNOLOGI INFORMASI SISTEM KEUANGAN DESA (SISKEUDES) DENGAN PENDEKATAN COSO DAN TAM - Afika Mardiyana Nur Khasanah; Bambang Widarno (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aims to examine the implementation of the Village Financial System (SISKEUDES) information technology by applying the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework and the Technology Acceptance Model (TAM) in Daleman Village, Lawu Village, and Baran Village, Sukoharjo Regency. By adopting a qualitative descriptive approach and triangulation methods, the research establishes that internal control mechanisms under the COSO guidelines are being applied productively. Such compliance is demonstrated through the mandatory cross-verification process conducted by the Financial Officer and Village Secretary, supported by the analytical capabilities of the system’s built-in audit trail. From the TAM perspective, village officials show a high level of technology acceptance, since the system is perceived to provide considerable ease of use and significant benefits in improving the efficiency of financial reporting. Nevertheless, several technical challenges remain, particularly server congestion during peak reporting periods. In addition, there is still a limitation in external transparency, as the dissemination of financial information through digital platforms such as village websites has not been optimally socialized to the community. As a result, many residents continue to rely on conventional information channels such as information boards and village meetings. Therefore, although internal accountability has been well established, improvements in digital infrastructure and communication strategies are necessary to strengthen transparency in village financial management